MHD convection flow of Ag-water nanofluid in inclined enclosure with center heater - Thangavelu, Mahalakshmi; Nagarajan, Nithyadevi; Öztop, Hakan Fehmi; Yang, Ruey-Jen (Oxford Univ Press, 2021)
Simulations are performed to examine magnetohydrodynamic convection of an Ag-water nanofluid within an inclined enclosure containing a center heater oriented in different directions. In performing the analysis, the left and right vertical walls are assumed to be isothermally cooled, while the bottom wall is isothermally heated and the top wall is adiabatic. The governing equations are solved numerically using the finite-volume method. The simulations focus on the effects of the Rayleigh number (Ra= 10(4), 10(5) and 10(6)), Hartmann number (Ha= 0, 25 and 50), inclination angle (gamma = 0 degrees, 45 degrees, 90 degrees and 135 degrees), orientation of heater (horizontal or vertical) and internal heat generation (S = 0, 10 and 20) on the convective heat transfer performance within the enclosure. The results show that the heat transfer performance is dominated by the inclination angleof the enclosure and theHartmannnumber. Inparticular, theheat transfer rate reduces as inclinationangle andHartmannnumber increase. The maximum heat transfer performance is obtained with a vertical center heater, an inclination angle of gamma = 45 degrees and a Rayleigh number of Ra = 10(6). It is additionally shown that the heat transfer performance improves with an increasing volume fraction of nanoparticles.
Keywords: magnetohydrodynamics; heat transfer; inclined enclosure; nanofluid